Entrepreneurial mindset and SME performance: The mediating role of entrepreneurial behavior - Juniardi; Sarwoko, Endi; Sahertian, Pieter (University of Islam Malang, 2023)
This study aims to examine the effect of an entrepreneurial mindset on SME performance and explore the mediating role of entrepreneurial behavior from an Attribution Theory perspective. The study explains that entrepreneurial behavior mediates entrepreneurial mindset and SME performance. This adds depth to the understanding of the mechanisms through which mindset impacts performance, shedding light on the importance of actual behavior in translating mindset into tangible outcomes. To accomplish these objectives, a quantitative research approach was adopted. Data were collected through a structured questionnaire administered to owners/managers of Micro, Small, and Medium Enterprises (MSMEs). To analyze the data and test the proposed hypotheses, Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed due to its suitability for exploring complex relationships with relatively small sample sizes. The dataset comprised responses from 382 owners/managers of MSMEs. Our findings suggest that while having an entrepreneurial mindset is crucial for performance, entrepreneurial behavior acts as the intermediary, guiding and directing the impact of mindset on actual business outcomes. In conclusion, by confirming Attribution Theory within the entrepreneurial context, this study extends the theory's applicability beyond traditional domains.